2015
DOI: 10.1589/jpts.27.1847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cervical flexion angle during smart phone use on muscle fatigue of the cervical erector spinae and upper trapezius

Abstract: [Purpose] The purpose of this study was to examine the influence of the cervical flexion angle when using a smart phone on muscle fatigue of the cervical erector spinae (CES) and upper trapezius (UT). [Subjects] This study recruited 12 healthy adults. [Methods] Each subject sat on a chair, with his/her back against the wall and held a smart phone with both hands. Fatigue of the neck and shoulder muscles at different cervical flexion angles (0°, 30°, and 50°) was measured by electromyography. The following musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 13 publications
1
36
0
3
Order By: Relevance
“…And, they claimed that the craniocervical flexion angle should be maintained at 30° rather than 50° or 0°. 23 The other study reported that UT muscle activity was also significantly decreased with increasing of craniocervical angle correction by taping during computer work. 8 These previous studies indicate that the degree of fatigue of UT is affected by the angle of the neck and the angle of the arm.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…And, they claimed that the craniocervical flexion angle should be maintained at 30° rather than 50° or 0°. 23 The other study reported that UT muscle activity was also significantly decreased with increasing of craniocervical angle correction by taping during computer work. 8 These previous studies indicate that the degree of fatigue of UT is affected by the angle of the neck and the angle of the arm.…”
Section: Discussionmentioning
confidence: 93%
“…Other previous study presented that higher shoulder flexion would increase risk of UT muscle activity level. 22 However, Lee et al 23 reported that the muscle fatigue of bilateral UT were highest at a cervical flexion angle of 50°…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al studied the relationship between activity of the upper trapezius and posture when a using smart phone. They found the alterations of muscle by electromyography (EMG) during cervical exion: The fatigue of the upper trapezius was − 0.2 ± 1.3 Hz at 0° neck exion and increased to − 3.5 ± 5.6 Hz at 50° [16]. Furthermore, for people with overhead work, the pressure-pain threshold of the upper trapezius was decreased by 1.4 lb after overhead work, which it veri ed that the ability of tolerance of pain was reduced when people had neck pain 35 .…”
Section: Alteration At Different Degrees Of Cervical Exionmentioning
confidence: 99%
“…People in certain professions such as computer and o ce workers have a higher risk of suffering from CNP. They usually sit for long periods with neck exion at a xed angle, which easily leads to discomfort and alteration of muscle fatigue [15][16]. The upper trapezius spanning the neck and shoulder is prone to structural muscle imbalance in poor posture.…”
Section: Introductionmentioning
confidence: 99%
“…Adult mobile phone usage was found to be one of the most important means of communication in an international study in 20071 ) . The rapid increase in the frequency of use of mobile phones among adults can adversely affect various aspects of human health, and numerous studies2,3,4 ) have investigated such adverse effects, particularly those focused on the neck and arms.…”
Section: Introductionmentioning
confidence: 99%